2022
DOI: 10.3389/fimmu.2022.835104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights Into the Immune Pathophysiology of COVID-19; An In-Depth Review

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), which causes coronavirus-19 (COVID-19), has caused significant morbidity and mortality globally. In addition to the respiratory manifestations seen in severe cases, multi-organ pathologies also occur, making management a much-debated issue. In addition, the emergence of new variants can potentially render vaccines with a relatively limited utility. Many investigators have attempted to elucidate the precise pathophysiological mechanisms causing COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 284 publications
0
24
0
Order By: Relevance
“…Furthermore, it was noted that key alterations in peripheral blood circulating B cell populations during the acute phase of SARS-CoV-2 infection were linked to the decreased levels of the relative and absolute number of B cells, increased frequencies of plasma cell precursors, atypical CD21-negative and activated B cells etc. [49,51,52]. Currently, we have shown that vitamin D supplementation could effectively decrease the relative numbers of activated CD38++CD27 transitional B cells and 'naïve' B cells in patients with acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was noted that key alterations in peripheral blood circulating B cell populations during the acute phase of SARS-CoV-2 infection were linked to the decreased levels of the relative and absolute number of B cells, increased frequencies of plasma cell precursors, atypical CD21-negative and activated B cells etc. [49,51,52]. Currently, we have shown that vitamin D supplementation could effectively decrease the relative numbers of activated CD38++CD27 transitional B cells and 'naïve' B cells in patients with acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, consolidations can represent ischemic regions. This overlap of viral, inflammatory, immune, and vascular events is clinically expressed by disease phenotypes with different prognostic weight [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 also features dysregulated neutrophil responses with increased NET production, contributing to the systemic inflammatory response syndrome and immunothrombosis in these patients ( 136 , 137 ). DM patients are known to be predisposed to severe COVID-19.…”
Section: Metformin and Netsmentioning
confidence: 99%